1995
DOI: 10.1515/znb-1995-1117
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenocenophanes

Abstract: The new dinuclear [1 .l] (5b) was also prepared and studied to gether with the corresponding [n]ferrocenophanes, 10a and 3a-5a. l,l'-Dilithioruthenocene was found to be a versatile starting material for the synthesis of silicon-substituted ruthenocene derivates such as Ru(C5H4-R)2 (R = SiMe3 (6b), Si2Me5 (7b)) and [n]ruthenocenophanes (3b-5b). A complete set o f 1H, 13C and 2 ,Si NMR data is presented, and the available structural data are discussed with respect to the tilt angle a of the cyclopentadienyl rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…This increasing separation has been attributed to an increased tilt angle α in several other cases, but in this study we could not confirm this trend. On the contrary, we found that in some cases Δ δ Cp decreases with increasing α: The [2]ruthenocenophane 3 (M=Ru, α =29.6(5)°) shows a separation of 0.38 ppm for the hydrogen atoms of the Cp ring,12 whereas for the analogous [2]ferrocenophane 3 (M=Fe, α =21.6(5)°)17 this value increases to δ =0.88 ppm 12. The same can be observed for 5 ( 5 : Δ δ Cp =0.34 ppm; 1 (ER n =ZrCp${{\prime \hfill \atop 2\hfill}}$ ): Δ δ Cp =0.37 ppm).…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…This increasing separation has been attributed to an increased tilt angle α in several other cases, but in this study we could not confirm this trend. On the contrary, we found that in some cases Δ δ Cp decreases with increasing α: The [2]ruthenocenophane 3 (M=Ru, α =29.6(5)°) shows a separation of 0.38 ppm for the hydrogen atoms of the Cp ring,12 whereas for the analogous [2]ferrocenophane 3 (M=Fe, α =21.6(5)°)17 this value increases to δ =0.88 ppm 12. The same can be observed for 5 ( 5 : Δ δ Cp =0.34 ppm; 1 (ER n =ZrCp${{\prime \hfill \atop 2\hfill}}$ ): Δ δ Cp =0.37 ppm).…”
Section: Methodsmentioning
confidence: 78%
“…Attempts to synthesize silicon‐bridged [1]ruthenocenophanes by reaction of the N , N , N ′, N ′‐tetramethylethylenediamine (TMEDA) adduct of dilithiated ruthenocene Ru(C 5 H 4 Li) 2 ⋅TMEDA ( 4 ) with Cl 2 SiMe 2 have been reported to result in the formation of dimeric and oligomeric species 11. 12 Introduction of larger elements such as zirconium or tin as the bridging atoms might be expected to lead to less‐strained and therefore more‐stable [1]ruthenocenophanes. We attempted to prepare the zirconium‐bridged [1]ruthenocenophane by the reaction of 4 with [Cl 2 ZrCp${{\prime \hfill \atop 2\hfill}}$ ] (Cp′=C 5 H 4 t Bu) in Et 2 O at low temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely however, the average value of b, the angle between each plane and the bridging atom-bridgehead bond, is slightly greater for [Me 2 Si(DMCh) 2 ]Fe (40.0°) than [Me 2 Si(C 5 H 4 ) 2 ]Fe (37.0°). This deviation from planarity of the sp 2 bridgehead atom of 1 is also reflected in its 13 C NMR resonance, which is found at d 47.4, an upfield shift relative to unbridged compounds. For comparison, the corresponding value for (DMCh) 2 Fe is d 77.9.…”
mentioning
confidence: 96%
“…The formation of 2 allows significant relief of the strain observed in the ansa-bridged species 1, as demonstrated by an angle a of 5.4°, and an average value of b of 6.5°. The silicon bridged cyclopentadienyl [1 2 ]ferrocenophane, {[Me 2 -Si(C 5 H 4 ) 2 ]Fe} 2 , which was reported simultaneously by three groups, [11][12][13] has a similar ring tilt [a = 4.9(3)°]. 12 In both cases, the ring tilt is opposite to that of the monomeric species; the greatest inter-ring separation is observed at the silicon-bridged end of the ring.…”
mentioning
confidence: 99%
“…Since the synthesis of the first [1.1]FCPs in 1956,7 this family of compounds has grown significantly with the incorporation of B,10 Al,11 Ga,11b, 12 In,11b, 13 Si,14 Sn,15 Pb,16 P,17 As,18 S,19 Zn,20 and Hg21 atoms as heteroatom bridges. In addition to these [1.1]FCPs, other [1.1]metallacyclophanes have been synthesized, such as [1.1]ruthenocenophanes,14a, 22 [1.1]chromarenophanes,23 [1.1]molybdarenophanes,23 and mixed [1.1]metallacyclophanes22 that contained Fe/Ru or Fe/Co metal combinations. In contrast to [1]metallacyclophanes, their formal dimers lack ring strain and no report of a successful ROP of [1.1]metallacyclophanes has been published to date.…”
Section: Introductionmentioning
confidence: 99%